Phase I, Randomized, Double‐blind, Placebo‐controlled, Single‐dose, and Multiple‐dose Studies of Erenumab in Healthy Subjects and Patients With Migraine. Issue 5 (24th October 2017) - de Hoon, Jan; Van Hecken, Anne; Vandermeulen, Corinne; Yan, Lucy; Smith, Brian; Chen, Jiyun Sunny; Bautista, Edgar; Hamilton, Lisa; Waksman, Javier; Vu, Thuy; Vargas, Gabriel
Abstract : Monoclonal antibodies (mAbs) targeting calcitonin gene‐related peptide (CGRP) signaling are being explored as prophylactic treatments for migraine. Erenumab (AMG 334) is the first potent, selective, and competitive human mAb antagonist of the CGRP receptor. We report the data from two phase I studies assessing the safety, pharmacokinetics (PK), and pharmacodynamics of single and multiple administrations of erenumab in healthy subjects and patients with migraine. The results indicate that the PK profile of erenumab is nonlinear from 1 mg to 70 mg and the linear portion of the clearance from 70 mg to 210 mg is consistent with other human immunoglobulin G2 antibodies. Single doses of erenumab resulted in >75% inhibition of capsaicin‐induced dermal blood flow, with no apparent dose‐dependency for erenumab ≥21 mg. Erenumab was generally well tolerated, with an acceptable safety profile, supporting further clinical development of erenumab for migraine prevention.